The Effect of Durian Fruit Waste Fermentated with Trichoderma Sp. in Laying Hen Ration on Egg Yolk Quality - Syaukani, Muhammad Fithrah Naufal; Ramadhan, Rahmad Fani; Adriani, Lovita (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Egg yolk has a high nutrient content, but cholesterol content and synthetic dyes added in egg yolk trigger concerns for the community so that alternatives are needed to improve egg quality by using Fermented Durian Fruit Waste (LBDF). This study aims to analyze the effect of LBDF with Trichoderma sp. in the ration of laying hens on egg quality. The research was conducted from January to March 2025 at Ciparanje Mini Feedmill and Laboratory of Non-Ruminant Poultry Nutrition and Animal Food Industry, located at Building 3, Faculty of Animal Husbandry, Padjadjaran University. The research was conducted experimentally using a completely randomized design (CRD) with 5 treatments and 4 replicates for each treatment, with each unit consisting of 2 laying hens, namely P0 (ration without LBDF), P1 (ration with LBDF Trichoderma sp. 5%), P2 (ration with LBDF Trichoderma sp. 10%), P3 (ration with LBDF Trichoderma sp. 15%), P4 (ration with LBDF  Trichoderma sp. 20%). The results showed that the addition of LBDF  with Trichoderma sp. gave a real effect on yolk cholesterol, yolk color, and yolk weight. The addition of LBDF to feed ingredients at 15% (P3) gave the best effect in reducing egg cholesterol, improving yolk color, and yolk weight.